'In Vitro' Comparison of K3XF and TFA Cyclic Fatigue Resistance in Continuous Rotation and Adaptive Motion - Carrillo-Várguez, A. G.; Carrillo-Várguez, L. H.; González-Vizcarra, B.; Villarreal-Gómez, L. J.; Valdez-Castro, R.; Cadena-Alcántar, M. A. (Revista Mexicana de Ingenieria Biomedica, 2018)
Among the most common problems within dental professionals, is the fracture of rotary instruments of nickel and titanium root canal files (NiTi), when performing a procedure on a patient. Therefore, the objective of this work is to compare the in vitro resistance to cyclic fatigue of K3XF and TFA rotatory instruments, in continuous rotation and adaptive motion. For this, a static and cyclic fracture test was used and a fracture pattern was searched. The numbers of cycles until the fracture and the length of the fragments were determined. Of all the groups evaluated, K3XF-A exhibited the best resistance to cyclic fatigue. In future research, it will be performed an autoclaving and immersion cycles in sodium hypochlorite to be able to determine the separation causes of the rotary instruments. As a recommendation, the operator could significantly influence the decrease in resistance to cyclic fatigue due to the misuse of rotary instruments.